Deliberation in a Democracy and Civic Education - Zaleskienė, Irena (Acta Paedagogica Vilnensia, 2005)
Author of the article presents the activities did run in the frame of transatlantic project ''Deliberation in A Democracy" and the results of evaluation of this project which was done by the team of evaluators from University of Minnesota (USA). During the 2004-05 school year, the Project was conducted with secondary teachers and their students in six sites: Azerbaijan, Czech Republic, and Lithuania, and the metropolitan areas surrounding Chicago, Los Angeles, and Washington, DC. The two overarching goals of the Project were stated to provide: (1) a model for secondary teachers to learn and appreciate among themselves the power of deliberation in their classrooms, and (2) a platform for engaging secondary students in discussions of substantive content on the institutions, governmental systems, and basic principles of a democratic constitutional state. Major activities associated with the project include: (1) teacher staff development workshops, (2) classroom deliberations, (3) an on-line Message Board for students and teachers, (4) a videoconference between students in partner sites, and (5) a teacher exchange. The results of the evaluative research (sample: 54 teachers and 1118 students participating in a project) are presented, and discussed. The methodology of research included two overlapping components. The first component is based on an adapted version of Thomas Guskey’s five-level model for evaluating professional development: (1) participants' reactions, (2) participants' learning, (3) organizational support and change, (4) participants’•use of new knowledge and skills, and (5) student learning outcomes. The second component of the evaluation design assesses implementation fidelity, documents the degree to which the Project achieved its stated outcomes. The analyses of the results leaded to conclusions about effectiveness of the project, because both the teacherss and the students learned a new way of discussion and it did make a statistically significant changes in student’s civic knowledge, political understanding and behaviour.
Keywords: civic education; deliberation in a democracy; meaningful debate skills; teleconference; virtual debate